Introduction to operations research - Hillier, Frederick S. (Holden-Day, 1986)
Without diluting any of the features of the sixth edition, the focus of the revision for the seventh edition is on increasing the motivation and excitement of the students by making the book considerably more "real-world" orientated and accessible. Twenty-five new cases have been added at the end of the problem sections, and new material includes eight new sections discussing the practical application of various techniques of operations research, a new chapter on project management with PERT/CPM, and many new problems. The CD-ROM provides an array of software options that reflect contemporary practice. --This text refers to an out of print or unavailable edition of this title.